2018
DOI: 10.1007/s13197-017-3009-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and anti-microbial properties of mutton nuggets incorporated with blends of essential oils

Abstract: The present study was carried out to evaluate effect of natural anti-oxidants on the quality of mutton nuggets. Different blends of essential oil were evaluated for incorporation in mutton nuggets and it was found that Blend-1 had significantly higher sensory scores. Then, Blend-1 was tried at 0.25, 0.5 and 0.75% levels and product containing 0.25% level received significantly higher sensory scores. Thereafter, two combinations of flaxseed flour and 0.25% Blend-1 were tried viz., 4% flaxseed flour + 0.25% Blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
4
17
1
Order By: Relevance
“…The results obtained were supported by the findings of Sharma, Mendiratta, Agarwal,Kumar, and Soni (2017), who observed a significantly (p < .05) higher DPPH value of fresh chicken sausage incorporated with 0.25% of clove essential oil than control during refrigerated storage for 20 days. The results also corroborated with the findings of Sharma, Mendiratta, Agrawal, Gurunathan,Kumar, and Singh (2017), who reported significantly higher (p < .05) DPPH free radical-scavenging activity in vacuum packed fresh chicken sausage incorporated with 0.25% of clove essential oil than control during frozen storage for 45 days Kumar , Mendiratta, Agrawal, Sharma, and Singh (2018). also reported a significantly higher (p < .05) DPPH activity of mutton nuggets incorporated with 0.25% blend of essential oils than control during refrigerated storage for 30 days.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained were supported by the findings of Sharma, Mendiratta, Agarwal,Kumar, and Soni (2017), who observed a significantly (p < .05) higher DPPH value of fresh chicken sausage incorporated with 0.25% of clove essential oil than control during refrigerated storage for 20 days. The results also corroborated with the findings of Sharma, Mendiratta, Agrawal, Gurunathan,Kumar, and Singh (2017), who reported significantly higher (p < .05) DPPH free radical-scavenging activity in vacuum packed fresh chicken sausage incorporated with 0.25% of clove essential oil than control during frozen storage for 45 days Kumar , Mendiratta, Agrawal, Sharma, and Singh (2018). also reported a significantly higher (p < .05) DPPH activity of mutton nuggets incorporated with 0.25% blend of essential oils than control during refrigerated storage for 30 days.…”
supporting
confidence: 89%
“…The results also corroborated with the findings of Sharma, Mendiratta, Agrawal, Gurunathan, Kumar, and Singh (2017), who reported significantly higher ( p < .05) DPPH free radical‐scavenging activity in vacuum packed fresh chicken sausage incorporated with 0.25% of clove essential oil than control during frozen storage for 45 days. Kumar , Mendiratta, Agrawal, Sharma, and Singh (2018) also reported a significantly higher ( p < .05) DPPH activity of mutton nuggets incorporated with 0.25% blend of essential oils than control during refrigerated storage for 30 days. Similarly, a significant increase ( p < .05) in DPPH free radical‐scavenging activity of beef steaks treated with sodium alginate coating incorporated with rosemary and oregano essential oil than control throughout the refrigeration storage for 14 days was also observed by Vital et al.…”
Section: Resultsmentioning
confidence: 85%
“…Lower TPC observed in treatment products than control may be attributed to the fact that when little oxygen was present, fewer oxidative changes could take place in the EOs and/or that cells obtaining energy via anaerobic metabolism are more sensitive to the toxic action of EOs. Variation in TPC among treatment products could be due to the difference in composition of different EOs combined in a blend (Kumar et al , 2018). EOs with aldehydes/phenols as major components are the most effective, followed by EOs containing terpene alcohols (Bassole and Juliani, 2012) while, EOs with ketones/esters possess lower activity (Dormans and Deans, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that naturally grazing sheep have more complex and diverse feeding behaviors than their barn-fed counterparts, and that this significantly affects the quality of animal products ( Webb and Erasmus, 2013 ). These differences are reflected in the growth performance, serum metabolites, antioxidant status, immune responses, and meat quality of sheep ( Dohme-Meier et al., 2014 ; Kumar et al., 2018 ; Watkins et al., 2014 ). One-third of the grasslands in China have been overgrazed since the 1970s, resulting in accelerated grassland degradation ( Akiyama and Kawamura, 2007 ).…”
Section: Introductionmentioning
confidence: 99%